Capacitor preparation method and capacitor
By immersing and drying the anode foil, cathode foil and electrolytic paper of the capacitor before the riveting, the problem that the dispersion is difficult to fully soak the core is solved, the immersion rate and quality of the capacitor are improved, and the performance of the capacitor is improved. and pressure resistance.
Patent Information
- Application Number
- CN202411417604.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
During the production process of solid-liquid hybrid capacitors, it is difficult for the dispersion liquid to fully soak the core, resulting in a lower pass rate of the core. Especially for large-volume cores, it is more difficult to achieve the ideal impregnation effect, affecting the performance of the capacitor.
Before riveting, the anode foil, cathode foil and electrolytic paper that are not riveted are respectively soaked in the dispersion liquid, and the water content after drying is controlled, and then riveting is carried out to ensure that the anode foil, cathode foil and electrolytics are performed. The paper is in contact with the dispersion sufficiently, thereby improving the permeability and quality.
By adjusting the wetting timing, the permeability of the anode foil, cathode foil and electrolytic paper is significantly improved, the quality and voltage resistance of the capacitor are improved, the difficulty of making large-volume capacitors is reduced, and the yield rate is improved.
Smart Images

Figure CN119296992A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitor production, and in particular to a method for preparing a capacitor and a capacitor. Background Art
[0002] Capacitors have a wide range of applications and are indispensable in intelligent, miniaturized and high-power devices. Traditional solid-state capacitors have the advantage of strong current bearing capacity, but they are difficult to manufacture, have a low pass rate, and are difficult to improve in voltage resistance. They also have poor automatic repair functions and are difficult to adapt to market needs.
[0003] On the basis of solid capacitors, solid-liquid hybrid capacitors have been introduced. Since solid-liquid hybrid capacitors have liquid electrolytes, they have a certain self-healing function during use. At present, when making solid-liquid hybrid capacitors, the anode foil, cathode foil and electrolytic paper are first riveted to form a core, and the core is soaked in the dispersion to achieve the attachment of conductive polymers. This processing method makes it difficult to soak the core with the dispersion, resulting in a low pass rate for the core. Especially for large-volume cores, it is more difficult to achieve an ideal soaking effect. Summary of the invention
[0004] The invention provides a method for preparing a capacitor and a capacitor, which are used to improve the penetration effect of a core, thereby improving the performance of the capacitor.
[0005] In a first aspect, the present invention provides a method for preparing a capacitor, comprising the following steps:
[0006] The un-riveted anode foil, the un-riveted cathode foil and the un-riveted electrolytic paper are respectively immersed in the dispersion liquid;
[0007] The impregnated anode foil, the impregnated cathode foil and the impregnated electrolytic paper are dried respectively.
[0008] riveting and rolling the dried anode foil, the dried cathode foil and the dried electrolytic paper to form a core;
[0009] The core is made into a capacitor.
[0010] In some implementations, the water content of the electrolytic paper after drying is greater than or equal to 5%.
[0011] In some implementations, the water content of the electrolytic paper after drying is 5% to 10%.
[0012] In some implementations, the moisture content of the anode foil after drying is greater than or equal to 5%, and the moisture content of the cathode foil after drying the dispersion is greater than or equal to 5%.
[0013] In some implementations, the moisture content of the dried anode foil, the dried cathode foil, and the dried electrolytic paper are all calculated according to the following formula:
[0014] A=(X-X0) / X0×100%,
[0015] Wherein, A is the water content, X is the mass of the dried anode foil, the dried cathode foil or the dried electrolytic paper, and X0 is the mass of the wetted anode foil, the wetted cathode foil and the wetted electrolytic paper.
[0016] In some implementations, the dispersion is a conductive polymer dispersion, and the conductive polymer dispersion contains polythiophene and deionized water.
[0017] In some implementations, the concentration of polythiophene in the conductive polymer dispersion is 50% to 90%.
[0018] In some implementations, when the anode foil, the cathode foil, and the electrolytic paper are riveted and rolled, the tension of the riveting roll is in the range of 0.1 MPa to 0.3 MPa.
[0019] In some implementations, before soaking the un-riveted anode foil or cathode foil in the dispersion, the following steps are also included:
[0020] Cutting the anode foil or cathode foil;
[0021] Treating the slit anode foil;
[0022] Cleaning the anode foil with a forming solution;
[0023] The anode foil after washing the chemical solution is dried.
[0024] In some implementations, the forming process of the cut anode foil comprises the following steps:
[0025] The cut anode foil is placed in an inorganic acid forming solution, and a forming voltage is applied to the anode foil, wherein the forming voltage is greater than or equal to 1.26 times the rated voltage of the capacitor and less than 1.4 times the rated voltage of the capacitor.
[0026] In some implementations, manufacturing the core formed by riveting and rolling into a capacitor comprises the following steps:
[0027] Drying the core;
[0028] impregnating the core into an electrolyte;
[0029] The impregnated core, capacitor housing and capacitor cover are assembled to form a capacitor.
[0030] In a second aspect, an embodiment of the present invention further provides a capacitor, which is manufactured according to the above-mentioned manufacturing method.
[0031] Compared with the prior art, the present invention has the advantage that, by placing the process of impregnating the dispersion liquid before the riveting and coiling process, the anode foil, cathode foil and electrolytic paper can be fully impregnated, thereby improving the impregnation effect of the dispersion liquid, thereby improving the quality of the anode foil, cathode foil and electrolytic paper. Even if the volume of the capacitor is large, the anode foil, cathode foil and electrolytic paper can be impregnated separately to achieve a higher impregnation rate of the anode foil, cathode foil and electrolytic paper, thereby improving the quality of the capacitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Hereinafter, the present invention will be described in more detail based on embodiments and with reference to the accompanying drawings.
[0033] Figure 1 is a flow chart of a method for preparing a capacitor in an embodiment of the present invention;
[0034] Figure 2 is a schematic structural diagram of a capacitor in an embodiment of the present invention;
[0035] Figure 3 is a flow chart of a method for preparing a capacitor including a step before infiltrating the dispersion in an embodiment of the present invention;
[0036] Figure 4 A flowchart of anode foil formation in an embodiment of the present invention;
[0037] Figure 5 is a flow chart of a method for preparing a capacitor in an embodiment of the present invention;
[0038] Figure 6 is a flow chart of a method for preparing a capacitor in an embodiment of the present invention;
[0039] Figure 7 is a flow chart of a method for processing an anode foil in an embodiment of the present invention;
[0040] Figure 8 FIG. 4 is a flow chart of a cathode foil processing method according to an embodiment of the present invention.
[0041] Reference numerals:
[0042] 1. Core;
[0043] 2. Aluminum shell;
[0044] 3. Cover plate;
[0045] 4. Casing;
[0046] 5. Electrolytic paper;
[0047] 6. Cathode foil;
[0048] 7. Anode foil;
[0049] 8. Positive lead terminal;
[0050] 9. Negative lead terminal. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with the accompanying drawings.
[0052] According to the type of electrolyte, capacitors can be divided into liquid capacitors, solid capacitors and solid-liquid hybrid capacitors. The electrolyte of the liquid capacitor is an electrolyte. Although the capacity and voltage are high, the service life is relatively short. The electrolyte of the solid capacitor is a solid conductive polymer. Compared with the liquid electrolyte, the conductivity of the solid conductive polymer is much higher than that of the liquid electrolyte, thereby reducing the resistance. In addition, the stability of the solid conductive polymer in a high temperature environment is higher than that of the liquid electrolyte. It is not easy to decompose at high temperature and is not easy to volatilize, which prolongs the service life of the solid capacitor. However, since its electrolyte is a solid conductive polymer, after the electrolyte is damaged, it cannot use the liquid electrolyte to repair the damaged oxide film like the liquid capacitor, and the self-healing property is poor. In order to combine the advantages of solid capacitors and liquid capacitors, a solid-liquid hybrid capacitor with inherent solid conductive polymers and liquid electrolytes has been introduced. It has good self-healing properties and is more stable than liquid capacitors in high temperature environments.
[0053] At present, when manufacturing solid-liquid hybrid capacitors, the anode foil 7, cathode foil 6 and electrolytic paper 5 are often riveted and rolled into a core 1, and then the core 1 is immersed in a dispersion containing a conductive polymer so that the conductive polymer adheres to the core 1. However, when the core 1 is immersed in the dispersion, basically only the outer surface of the core 1 can contact the dispersion, and it is difficult to penetrate the core 1, which makes it difficult for the solid conductive molecules to fully adhere to the outer surfaces of the anode foil 7, cathode foil 6 and electrolytic paper 5, resulting in a low pass rate of the core 1.
[0054] In order to solve the problem that the dispersion liquid of the solid-liquid hybrid capacitor is not fully infiltrated and the qualified rate of the core 1 is low, the present application provides a method for preparing a capacitor, see Figure 1 and Figure 2 As shown, the preparation method comprises the following steps:
[0055] Solid polymer dispersion infiltration: infiltrating the unwound anode foil 7, the unwound cathode foil 6 and the unwound electrolytic paper 5 into the dispersion;
[0056] Drying the polymer after impregnation: drying the impregnated anode foil 7, the impregnated cathode foil 6 and the impregnated electrolytic paper 5 with the dispersion, wherein the water content of the electrolytic paper 5 after the dispersion drying is greater than or equal to 5%;
[0057] Riveting and rolling: using the dried anode foil 7, the dried cathode foil 6 and the dried electrolytic paper 5 to rivet and roll into a core 1;
[0058] And a capacitor is made by using the core 1 formed by riveting and rolling.
[0059] By setting the solid polymer dispersion infiltration process before riveting and coiling, the unriveted anode foil 7 can be fully infiltrated in the solid polymer dispersion. Compared with the core 1 after riveting and coiling, the unriveted anode foil 7 is immersed in the dispersion and the contact area with the dispersion is larger, which can significantly improve the permeability of the anode foil 7. Similarly, the unriveted cathode foil 6 and the unriveted electrolytic paper 5 are immersed in the dispersion, which can also improve the permeability of the cathode foil 6 and the electrolytic paper 5. That is to say, in the present application, by adjusting the timing of infiltrating the dispersion, the permeability of the anode foil 7, the cathode foil 6 and the electrolytic paper 5 in the capacitor can be improved, so that the solid polymer is more fully attached to the anode foil 7, the cathode foil 6 and the electrolytic paper 5.
[0060] Furthermore, when the electrolytic paper 5 is dried, the water content of the electrolytic paper 5 is controlled to be greater than or equal to 5%, so that the excess water not attached to the outside of the electrolytic paper 5 can be removed to reduce the volume of the electrolytic paper 5, and the electrolytic paper 5 can be kept relatively soft as a whole containing water, so that the high molecular substances on the surface of the electrolytic paper 5 can be prevented from falling off, and the electrolytic paper 5 can be avoided from being damaged due to severe deformation during riveting, thereby improving the qualified rate of the solid-liquid hybrid capacitor.
[0061] In addition, due to the high permeability of the dispersion, the difficulty of manufacturing large-volume solid-liquid hybrid capacitors is greatly reduced, thereby significantly improving the withstand voltage of the solid-liquid hybrid capacitors and improving the yield of large-volume solid-liquid hybrid capacitors.
[0062] The anode foil 7 is one of the two plates of the capacitor, plays a conductive role and absorbs positive charges. When the capacitor is prepared by the preparation method provided by the present application, the anode foil 7 selected for the liquid solder sheet electrolytic capacitor under the same rated voltage can be selected.
[0063] The specific volume of cathode foil 6 is much higher than that of anode foil 7. Generally, the specific volume of cathode foil 6 is more than 10 times that of anode foil 7, thereby increasing the utilization rate of anode foil 7. In addition, the thickness of cathode foil 6 is generally 20 μm.
[0064] The electrolytic paper 5 can be a two-layer composite electrolytic paper 5, preferably the two layers of the electrolytic paper 5 have different thicknesses, densities and withstand voltages. The main function of the electrolytic paper 5 is to be placed between the anode foil 7 and the cathode foil 6 to prevent the plates from directly contacting each other and short-circuiting, and to better absorb the electrolyte.
[0065] It should be noted that, in the process of riveting and reeling, not only the anode foil 7, cathode foil 6 and electrolytic paper 5 are needed, but also materials such as foil guide strips and adhesive tapes are needed. The anode foil 7, cathode foil 6, electrolytic paper 5, foil guide strips and adhesive tapes are cold welded and reeled by a riveting and reeling machine to form a core 1 with the anode foil 7, cathode foil 6, electrolytic paper 5, foil guide strips and adhesive tapes.
[0066] The moisture content of the dried anode foil, the dried cathode foil and the dried electrolytic paper are calculated according to the following formula:
[0067] A=(X-X0) / X0×100%,
[0068] Wherein, A is the water content, X is the mass of the dried anode foil, the dried cathode foil or the dried electrolytic paper, and X0 is the mass of the wetted anode foil, the wetted cathode foil and the wetted electrolytic paper.
[0069] The water content of the electrolytic paper 5 can be calculated by weighing the mass X0 of the electrolytic paper 5 after being soaked and the mass X of the electrolytic paper 5 after being dried during the drying process, ensuring that the water content of the electrolytic paper 5 after drying is greater than or equal to 5%.
[0070] In the related art, when drying the anode foil 7, cathode foil 6 and electrolytic paper 5, the anode foil 7, cathode foil 6 and electrolytic paper 5 can be dried by placing the anode foil 7, cathode foil 6 and electrolytic paper 5 in a drying device. The temperature of the drying device can be set at about 95°C during drying.
[0071] In some implementations, the water content of the anode foil 7 after the dispersion is dried is greater than or equal to 5%, and the water content of the cathode foil 6 after the dispersion is dried is greater than or equal to 5%.
[0072] That is to say, not only the electrolytic paper 5 retains some moisture after drying, but the anode foil 7 and the cathode foil 6 also retain moisture after drying, which can make them easier to deform during the riveting and coiling process, thereby reducing the risk of damage to the anode foil 7 and the cathode foil 6 during the riveting and coiling process or the risk of the solid polymer on the surface falling off, thereby improving the yield rate of the solid-liquid hybrid capacitor.
[0073] In some implementations, the water content of the electrolytic paper 5 after the dispersion is dried is 5% to 10%. By controlling the water content of the electrolytic paper 5, the volume increase caused by excessive water in the electrolytic paper 5 is avoided, which is conducive to the miniaturization of the battery cell and the capacitor.
[0074] In some implementations, the dispersion contains polythiophene and deionized water. Polythiophene has good electrical conductivity. By soaking the anode foil 7, cathode foil 6 and electrolytic paper 5 in the dispersion containing polythiophene, polythiophene is attached to the outside of the anode foil 7, cathode foil 6 and electrolytic paper 5, thereby significantly improving the electrical conductivity of the anode foil 7, cathode foil 6 and electrolytic paper 5. Soaking the anode foil 7, cathode foil 6 and electrolytic paper 5 in the dispersion containing polythiophene can reduce the ESR and loss angle of the capacitor, reduce the heat generation of the capacitor, and improve the ripple current resistance of the capacitor, so that the performance of the capacitor is significantly improved.
[0075] In some implementations, the concentration of polythiophene in the dispersion is 50-90%. That is, every 100g of the dispersion contains 50g-90g of polythiophene. The dispersion contains a high concentration of polythiophene, and when the anode foil 7, the cathode foil 6 and the electrolytic paper 5 are infiltrated with the dispersion, more polythiophene can be attached to the outside of the anode foil 7, the cathode foil 6 and the electrolytic paper 5. The particle size of the polythiophene is 10-150nm.
[0076] In some implementations, when the anode foil 7, cathode foil 6 and electrolytic paper 5 are riveted, the tension of the riveting coil is in the range of 0.1MPa to 0.3MPa, where the tension refers to the tension applied by the riveting coiling machine to the anode foil 7, cathode foil 6 and electrolytic paper. Compared with the conventional riveting coil tension of 0.15 to 0.5Mpa of the cathode foil 6, anode foil 7 and electrolytic paper 5, the anode foil 7, cathode foil 6 and electrolytic paper 5 with the conductive polymer attached can be prevented from being damaged, and the conductive polymer can be prevented from falling off the anode foil 7, cathode foil 6 and electrolytic paper 5. Among them, the riveting coil tension is preferably 0.1MPa to 0.15MPa, which is lower than the minimum value of the conventional riveting coil tension.
[0077] See also Figure 1-Figure 3 As shown, in some implementations, before the un-riveted anode foil 7 is immersed in the dispersion, the following steps are also included:
[0078] Cutting the anode foil 7 or the cathode foil 6;
[0079] The cut anode foil 7 is subjected to chemical treatment;
[0080] Cleaning the anode foil 7 with a forming solution;
[0081] Anode foil 7 after washing the chemical conversion solution is dried.
[0082] When the anode foil 7 is cut, the anode foil 7 and the electrolytic paper 5 can be cut at the same time, and the material can be cut into a certain width according to the specifications and volume requirements of the welding sheet aluminum electrolytic capacitor. It should be noted that, since the anode foil 7, the cathode foil 6 and the electrolytic paper 5 are first soaked in the dispersion in the present application, and then the anode foil 7, the cathode foil 6 and the electrolytic paper 5 are riveted and rolled into the core 1, there is no need to reduce the volume of the anode foil 7 and the cathode foil 6 to adapt to the riveting and rolling process. The anode foil 7 and the cathode foil 6 can be cut into the same width as the welding sheet during cutting, and can also adapt to the specifications of large-volume welding sheets.
[0083] By chemically treating the anode foil 7, oxygen atoms in water can be combined with aluminum atoms in the anode foil 7, thereby forming an oxide film capable of withstanding a specific voltage on the surface of the anode foil 7. At the same time, by chemically treating the anode foil 7, some defects on the surface of the original oxide film can also be repaired.
[0084] When the chemical solution for cleaning the anode foil 7 is used, deionized water may be used to clean the anode foil 7 , wherein the purity of the deionized water is required to be ≥1 MΩ.
[0085] In some implementations, the chemical treatment of the cut anode foil 7 includes the following steps:
[0086] The cut anode foil 7 is placed in an inorganic acid forming liquid, wherein the inorganic acid in the inorganic acid forming liquid can be boric acid, and the content of the inorganic acid in the forming liquid is 1-5%.
[0087] In other implementations, the electrolyte may further include a solvent, a solute, and an additive, wherein the solvent includes at least one of ethylene glycol, water, glycerol, benzyl alcohol, GBL, and DMF, and the solute includes at least one of adipic acid, ammonium adipate, ammonium formate, triethylamine, amidine salts, sebacic acid, ammonium sebacic acid, dodecanedioic acid, ammonium dodecanedioate, ammonium hydrogen azelaic acid, and branched organic ammonium salts;
[0088] See also Figure 3 and Figure 4 As shown, the anode foil 7 placed in the formation solution is energized, and the formation voltage is greater than or equal to 1.26 times the rated voltage of the capacitor and less than 1.4 times the rated voltage of the capacitor. For example, when the rated voltage of the capacitor is 400VDC, the formation voltage can be controlled at 504VDC to 560VDC.
[0089] When anode foil 7 is pressurized and formed, the forming temperature is 70° C. to 95° C.
[0090] In some implementations, see Figure 1 and Figure 5 As shown, the solid-liquid hybrid capacitor is made by using the core 1 formed by riveting and rolling, including the following steps:
[0091] Drying the core 1;
[0092] Immersing the core 1 in the electrolyte;
[0093] The impregnated core 1 is assembled with a capacitor case to form a solid-liquid hybrid capacitor.
[0094] When the core 1 is dried, a tunnel oven can be used to dry the core 1 at a drying temperature of 95° C. for 4 hours.
[0095] The dried core 1 is impregnated with online hydraulic pressure, with vacuum and hydraulic pressure alternately performed, the vacuum degree reaches about -0.098MPa, the pressure reaches above 1MP, and the time is 0.5 hour to 1 hour. The electrolyte is fully adsorbed on the electrolytic paper 5, the anode foil 7 and the cathode foil 6, ensuring that there is sufficient electrolyte consumption in the capacitor core 1.
[0096] The core 1 impregnated with electrolyte is directly assembled with the capacitor housing, the cover plate 3 and the sleeve to form a capacitor. The process of assembling the capacitor is consistent with that of a conventional electrolytic capacitor.
[0097] A specific process of assembling a capacitor may include assembling a seal and a sleeve.
[0098] Among them, the assembly sealing is to rivet the impregnated core 1 onto the cover plate 3, and install the core 1 with the riveted cover plate 3 into the corresponding aluminum shell 2. By performing the waisting process and the crimping process on the aluminum shell 2, the capacitor is sealed to ensure that the inside of the capacitor is separated from the external environment.
[0099] The casing process refers to putting a casing of corresponding specifications on the bare product and distinguishing the positive and negative poles. At the same time, the relevant specification information will be printed on the outside of the capacitor to facilitate the identification of the specification information of the capacitor when using it.
[0100] In some implementations, after the capacitor is assembled, aging and sorting are also included. When aging the capacitor, a fully automatic aging and sorting machine can be used to repair the oxide film damaged during the riveting process and the defects of the original oxide film.
[0101] Sorting is to remove defective capacitors. For accurate sorting, the aged capacitors need to be placed at room temperature to recover for several hours. After the internal performance of the capacitors is stable, 100% sorting can be carried out to remove defective capacitors.
[0102] The ESR (Equivalent Series Resistance) of the solid-liquid hybrid capacitor prepared by this preparation method is 1 / 5 to 1 / 10 of the ESR of conventional capacitors of the same specifications, and the current bearing capacity of the prepared capacitor can reach more than 3 times that of conventional capacitors. For example, using the same 400V820UF 30*60 specification capacitor, the ESR of the conventional capacitor is about 0.1Ω, and the ripple current withstand is about 2.5A. The ESR of the solid-liquid hybrid capacitor made by the preparation method provided in this application can be reduced to about 0.015Ω, and the ripple current withstand can reach more than 7.5A.
[0103] That is to say, if the same filtering function needs to be achieved, three capacitors may be needed in the past, but only one is needed after replacing it with the solid-liquid hybrid capacitor made in this embodiment, which greatly reduces the number of capacitors and is conducive to the miniaturization of the equipment.
[0104] For easier understanding, see Figure 2 as well as Figure 6 As shown, the complete preparation method of the solid-liquid hybrid capacitor in this embodiment can be referred to the following embodiment.
[0105] S01: Material cutting: specifically including the cutting of anode foil 7, cathode foil 6 and electrolytic paper 5. By cutting the anode foil 7, cathode foil 6 and electrolytic paper 5, the anode foil 7, cathode foil 6 and electrolytic paper 5 can be cut into suitable sizes for subsequent use.
[0106] S02: Formation process: the cut anode foil 7 is inserted into the inorganic acid forming liquid, and the high voltage power supply of the forming equipment is used to pressurize the anode foil 7, so as to repair the aluminum oxide film damaged in the cutting process, and at the same time, the gas oxide film defects on the surface of the anode foil 7 can be repaired, so as to ensure that the surface of the anode foil 7 is completely covered with the aluminum oxide layer, wherein the forming temperature of the forming process is preferably 70°C to 95°C. The concentration of the inorganic acid in the forming liquid is preferably 1% to 5%.
[0107] S03: Cleaning: Clean the formed anode foil 7 with deionized water to remove the formed liquid on the surface of the anode foil 7, especially to remove the residual liquid of inorganic acid on the surface of the anode foil 7.
[0108] S04: Drying the anode foil 7 after formation: Drying the cleaned anode foil 7 by a drying device, wherein the drying temperature is greater than or equal to 95° C., so as to remove moisture on the surface of the anode foil 7 .
[0109] S05: Infiltration with solid polymer dispersion: the formed anode foil 7, the unwound cathode foil 6 and the unwound electrolytic paper 5 are infiltrated with solid polymer dispersion, so that the anode foil 7, the cathode foil 6 and the electrolytic paper 5 are attached with solid conductive polymer, thereby improving the conductivity of the anode foil 7, the cathode foil 6 and the electrolytic paper 5, thereby improving the performance of the capacitor, so that the solid-liquid hybrid capacitor can withstand high voltage (above 400V, or above 600V).
[0110] S06: Dry the anode foil 7, cathode foil 6 and electrolytic paper 5 soaked in the dispersion, and ensure that the water content of the electrolytic paper 5 is greater than or equal to 5%. Drying can be done by drying equipment at a temperature of 95° C. Since the electrolytic paper 5 still contains a certain amount of water after drying, the electrolytic paper 5 is relatively soft and can adapt to the bending during riveting.
[0111] S07: riveting and rolling to form core 1: the dried anode foil 7, the dried cathode foil 6 and the dried electrolytic paper 5 are riveted and rolled with conductive foil strips, adhesive tapes, etc. through a riveting and rolling machine to form core 1, so that the anode foil 7, the cathode foil 6 and the electrolytic paper 5 are closely attached. Since the water content of the electrolytic paper 5 is greater than 5%, the shedding of the conductive polymer on the surface of the material during the riveting and rolling process can be reduced.
[0112] S08: drying the core 1, drying the riveted coiled core 1 in a tunnel oven, wherein the drying temperature is 95°C and the drying time is 0.5 to 1 hour.
[0113] S09: Impregnation: The core 1 is immersed in the electrolyte by online hydraulic impregnation, so that the electrolytic paper 5 in the core 1 fully absorbs the electrolyte.
[0114] S10: Assemble and seal, rivet the impregnated core 1 onto the cover plate 3, and install the core 1 with the riveted cover plate 3 into the corresponding aluminum shell 2, and seal the capacitor by waisting and crimping the aluminum shell 2.
[0115] S11: Casing, the specification information of the capacitor is printed on the outside of the capacitor, and the positive and negative poles of the capacitor are distinguished by the casing.
[0116] S12: Aging, using a fully automatic aging sorting machine to repair the oxide film damaged during the riveting process.
[0117] S13: Sorting: place the aged capacitors at room temperature for several hours, and screen the capacitors after the internal structure of the capacitors is stable, and remove the defective capacitors.
[0118] Among them, in steps S05-S06, the riveting and coiling process is placed after the impregnation with the dispersion liquid. Compared with riveting and coiling first and then impregnating with the dispersion liquid, the dispersion liquid penetration effect of the anode foil 7, cathode foil 6 and electrolytic paper 5 in the core 1 is improved, and more surfaces of the anode foil 7, cathode foil 6 and electrolytic paper 5 can be impregnated with the dispersion liquid, thereby improving the conductivity of the anode foil 7, cathode foil 6 and electrolytic paper 5, thereby improving the withstand voltage capability of the capacitor. In addition, since the infiltration of the dispersion liquid is completed before riveting and coiling, the infiltration effect is independent of the specifications of the core 1, and a larger core 1 and a larger capacitor can be manufactured without affecting the conductivity of the anode foil 7, cathode foil 6 and electrolytic paper 5, thereby improving the performance of the capacitor by increasing the material, and further improving the withstand voltage performance of the capacitor.
[0119] In a second aspect, the present invention further provides a capacitor, which is manufactured using the above-mentioned method for preparing the solid-liquid hybrid capacitor.
[0120] The capacitor manufactured by the method not only has the anode foil 7, cathode foil 6 and electrolytic paper 5 with excellent conductive properties, but also has a high yield rate, thereby greatly reducing the cost of mass production of capacitors.
[0121] See also Figure 2 As shown, the capacitor further comprises a bushing 4, and a positive lead terminal 8 and a negative lead terminal 9 are arranged on the cover plate.
[0122] Although the present invention has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a capacitor, characterized in that: It includes the following steps: The un-riveted anode foil, the un-riveted cathode foil and the un-riveted electrolytic paper are respectively immersed in the dispersion liquid; The impregnated anode foil, the impregnated cathode foil and the impregnated electrolytic paper are dried respectively. riveting and rolling the dried anode foil, the dried cathode foil and the dried electrolytic paper to form a core; The core is made into a capacitor.
2. The preparation method according to claim 1, characterized in that: The water content of the electrolytic paper after drying is greater than or equal to 5%.
3. The preparation method according to claim 2, characterized in that: The water content of the electrolytic paper after drying is 5% to 10%.
4. The preparation method according to claim 1, characterized in that: The moisture content of the anode foil after drying is greater than or equal to 5%, and the moisture content of the cathode foil after drying the dispersion is greater than or equal to 5%.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The moisture content of the dried anode foil, the dried cathode foil and the dried electrolytic paper are calculated according to the following formula: A=(X-X0) / X0×100%, Wherein, A is the water content, X is the mass of the dried anode foil, the dried cathode foil or the dried electrolytic paper, and X0 is the mass of the wetted anode foil, the wetted cathode foil and the wetted electrolytic paper.
6. The preparation method according to claim 1, characterized in that: The dispersion is a conductive polymer dispersion, which contains polythiophene and deionized water.
7. The preparation method according to claim 6, characterized in that: The concentration of polythiophene in the conductive polymer dispersion is 50% to 90%.
8. The preparation method according to claim 1, characterized in that: When the anode foil, the cathode foil and the electrolytic paper are riveted and rolled, the tension of the riveting roll is in the range of 0.1 MPa to 0.3 MPa.
9. The preparation method according to any one of claims 1 to 4, characterized in that: Before soaking the un-riveted anode foil or cathode foil in the dispersion, the method further comprises the following steps: Cutting the anode foil or cathode foil; Treating the slit anode foil; Cleaning the anode foil with a forming solution; The anode foil after washing the chemical solution is dried.
10. The preparation method according to claim 9, characterized in that: The anode foil after slitting is treated by chemical treatment, comprising the following steps: The cut anode foil is placed in an inorganic acid forming solution, and a forming voltage is applied to the anode foil, wherein the forming voltage is greater than or equal to 1.26 times the rated voltage of the capacitor and less than 1.4 times the rated voltage of the capacitor.
11. The preparation method according to any one of claims 1 to 4, characterized in that: The core formed by riveting coils is made into a capacitor, comprising the following steps: Drying the core; impregnating the core into an electrolyte; The impregnated core, capacitor housing and capacitor cover are assembled to form a capacitor.
12. A capacitor, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 11.